2001
DOI: 10.1017/s0033822200041692
|View full text |Cite
|
Sign up to set email alerts
|

The Cave of Theopetra, Kalambaka: Radiocarbon Evidence for 50,000 Years of Human Presence

Abstract: The cave of Theopetra is located on the northeast side of a limestone rock formation, 3 km south of Kalambaka (21°40′46′′E, 39°40′51′′N), in Thessaly, central Greece. It is a unique prehistoric site for Greece, as the Middle and Upper Paleolithic, Mesolithic, and Neolithic periods are present here, bridging the Pleistocene with the Holocene. Several alternations of the climate during the Pleistocene are recognized in its stratigraphy. Among the most striking finds, two human skeletons, one from the Upper Paleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As is the case in other regions as well, it is very difficult to trace the ephemeral remains of highly mobile groups of people, except in caves where they have been protected from both erosion and alluvial or colluvial coverage. That Mesolithic populations indeed used the terrestrial and marine resources in the region of Thessaly is demonstrated by the two caves situated in its far west (Theopetra: compare Kyparissi-Apostolika 2000a;2000b;Facorellis et al 2001) and far east (Cyclops Cave on the island of Youra: compare Sampson et al 2003;Facorellis et al 1998). …”
Section: The End Of the Mesolithic And Beginning Of The Neolithic In mentioning
confidence: 98%
“…As is the case in other regions as well, it is very difficult to trace the ephemeral remains of highly mobile groups of people, except in caves where they have been protected from both erosion and alluvial or colluvial coverage. That Mesolithic populations indeed used the terrestrial and marine resources in the region of Thessaly is demonstrated by the two caves situated in its far west (Theopetra: compare Kyparissi-Apostolika 2000a;2000b;Facorellis et al 2001) and far east (Cyclops Cave on the island of Youra: compare Sampson et al 2003;Facorellis et al 1998). …”
Section: The End Of the Mesolithic And Beginning Of The Neolithic In mentioning
confidence: 98%
“…A trace fossil is defined as "a morphologically recurrent structure resulting from the life activity of an individual organism (or homotypic organism) modifying the substrate" (Bertling et al, 2006:266). From an archaeological perspective, traces include signs of human biology such as footprints (Roberts & Berger, 1997;Facorellis, Kyparissi, & Maniatis, 2001;Zhang & Li, 2002;Mietto, Avanzini, & Rolandi, 2003;Webb, Cupper, & Robins, 2006;Bennett et al, 2009) and feces (i.e., Callen, 1969;Bryant, 1974;Bryant & Williams-Dean, 1975;Reinhard & Bryant, 1992), as well as signs of predation (bite and gnaw structures). However, signs of human technology and pathological structures are not considered traces.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of calibrated C-14 dates during the Upper Paleolithic and Neolithic until present from excavated lithologies in the Thessalian Theopetra Cave (Facorellis et al 2001). Note the data of charcoal infill from the layer just below the overlain Neolithic lithologies (Fig.17), as well as the time gap of more than 1000 years during the cold Younger Dryas period.…”
Section: Fig 19mentioning
confidence: 99%